2009
DOI: 10.4317/medoral.15.e90
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of two acid solutions and 2.5% sodium hypochlorite used in endodontic therapy

Abstract: Navarro-Escobar E, González-Rodríguez MP, Ferrer-Luque CM. Cytotoxic effects of two acid solutions and 2.5% sodium hypochlorite used in endodontic therapy. Med Oral Patol Oral Cir Bucal. 2010 Jan 1;15 (1):e90-4.http://www.medicinaoral.com/medoralfree01/v15i1/medoralv15i1p90.pdf AbstractAim: To evaluate the cytotoxicity of 15% citric acid, 5% phosphoric acid and 2.5% NaOCl on cultured fibroblasts using MTT colorimetric assay. Methodology: Irrigating solutions of 5% phosphoric acid, 15% citric acid, and 2.5% NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…These results are in agreement with Navarro‐Escobar et al . (), who evaluated cell viability by MTT at 24 h of 2.5% NaOCl in two dilutions, 0.1% and 0.5% on fibroblasts (NIH/3T3) and also found a significant reduction in 0.5%, only 0.1% dilution had higher levels of cell viability. Regarding CHX, Lessa et al .…”
Section: Discussionmentioning
confidence: 93%
“…These results are in agreement with Navarro‐Escobar et al . (), who evaluated cell viability by MTT at 24 h of 2.5% NaOCl in two dilutions, 0.1% and 0.5% on fibroblasts (NIH/3T3) and also found a significant reduction in 0.5%, only 0.1% dilution had higher levels of cell viability. Regarding CHX, Lessa et al .…”
Section: Discussionmentioning
confidence: 93%
“…Thus, several studies have been carried out in order to compare the cytotoxic effects with those of other irrigant solutions. Regarding this aspect, Navarro-Escobar et al (12) compared the cytotoxicity of 15% citric acid, 5% phosphoric acid and 2.5% NaOCl. They concluded that the irrigating solution with the highest percentage of cell viability was 2.5% NaOCl at both 0.1% and 0.5% dilu-tions.…”
Section: Discussionmentioning
confidence: 99%
“…Ishod endodontskog zahvata tako ovisi o vrsti i broju zaostalih mikroorganizama (5). Najčešće rabljeno sredstvo za dezinfekciju i irigaciju korijenskih kanala jest natrijev hipoklorit (NaOCl).…”
Section: Janković I Surunclassified
“…The outcome of treatment depends on the type and number of residual microorganisms (5). The most commonly used root canal irrigation solution is sodium hypochlorite (NaOCl).…”
Section: Janković I Surmentioning
confidence: 99%